Memoria : an exploration of longing, desire and transcience in the everyday - Simon, Janet (Michaelis School of Fine Art, 2017)
This is a very personal body of work from a specifically feminine perspective. I have felt enormous pressure for most of my life to try to maintain what I believe to be an acceptable appearance. I have struggled with my weight and with acne for many years. As a result, I have constantly feared being photographed or being seen without my usual mask of makeup. This has caused me to feel a disjuncture between my inner self and my outward appearance. I have become acutely aware of the face as a mask that can be manipulated in many ways, and of the illusion that lies beneath appearances. As a reaction to what I perceive to be an enormous emphasis on flawless appearances and beauty, in, for example advertising, magazines and film, I have been drawn to the overlooked, the discarded and the decayed in the everyday When sourcing material for this body of work, I have wanted to explore that which I habitually overlook in my everyday life; which has become so familiar that it is rarely noticed. I have particularly wanted to examine the significance of the everyday.